The International Legal Regime for Biotechnology Patenting: an Appraisal from the Standpoint of Developing Countries - Badimboli Atibasay, Jean-Faustin (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2001)
The development of biotechnology, which promises many economic opportunities, has revived the debate over the ownership of biological resources and its derivatives, as well as the sharing of the benefits which derive from its multiple applications. At the core of the debate, is the recent marriage between intellectual property rights (IPR) and international trade, within the framework of the World Trade Organization (WTO). In this context, the need of developed countries to prevent trade distortions due to the lack of adequate IPR protection in developing countries, is weighed against the need to promote local interests in these countries.However, the legal impact of recent multilateral agreements, which address biological innovations, is still subject to controversy. An assessment of these instruments reveals divergent approaches to the issues which divide the parties concerned. This results in ambiguities and conflicts with respect to relevant provisions of these agreements.From a wide range of possible solutions discussed, industrial and developing countries might consider to review the disputed provisions in a way that attempts to harmonise the agreements and render legal implications of their respective initiatives in this area more predictable.